A Study on Depression in Returnee Female Migrant Workers - Singh, Pradip Man; Joshi, Neelam; Prajapati, Anita (Journal of BP Koirala Institute of Health Sciences, 2020)
Introduction: Women seeking foreign employment have been rising in Nepal. Changing scenarios, like: household structure and women's desire to work outside have provided opportunity for women from countries like Nepal to become independent and give financial support in family. For female migrant workers, it is not easy to adjust to new country because of difference in socio-cultural aspect, poor working and living condition. Many of them suffer from health issues including psychiatric morbidity. Objective: To estimate the prevalence of depression and the socio-demographic profiles of returnee female Nepalese migrant workers. Methods: A descriptive study was undertaken in Emergency Shelter House of an NGO, among returnee female migrant workers using semi-structured questionnaire, interview and Hamilton’s Depression Rating Scale (HAM-D). Ethical clearance and consent were taken. Results: The HAM-D score showed that 71.5% of the subjects were depressed which was analyzed with various socio-demographic profiles and the factors of foreign employment. A strong significance was seen with residential area (p= 0.004). The level of depression was not statistically significant with age, education, marital status, earning of husband and monthly household income. Conclusion: Depressive symptoms were common among returnee female migrant workers. Regular mental health assessment of returnee women migrant workers should be done. This will help to minimize the psychiatric morbidity among them.